(3JMQjQ cJGH GdeYWjGJs - (3GbdjOSs
(3ChdgG (B:s
(3GdSWhM hGdNWhW hGdRhGjG GdeYdheI hGdNWhW GdeYdeI GdUhQI gi GdJi Jchf RhGjGgG eYdheI hfSH GdCVdGY HYVgG Edi HYV eYdheI s
(3BNQgG (B:s
(3hbO eQefgG CM HfbWI Q GdeYdheI Je cJGH GdeYWjGJ hddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1460s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs